A new stylus orientation planning strategy for sculpture surface inspection based on touch position graph. (August 2022) - Wan, Neng; Zhuang, Qixin; Guo, Yanheng; Chen, Zezhong C.; Fang, Zixi
Highlights: On-machine inspection is an important technology for decreasing fabrication errors. We propose a new on-machine measurement strategy that controls the practical touch position on stylus tip for multi-axis on-machine inspection. We investigate a touch position graph to discover the relationship between the practical touch positions and the stylus orientations. The proposed approach can plan the least touch positions on the stylus tip and reduce the rotation direction change of the rotary axes of the machine tool to improve the inspection accuracy and efficiency. Abstract: On-machine inspection (OMI) is an important technology for precise machining. Accuracy and efficiency improvement is a challenge for sculpture surface inspection. Before the inspection, if the practical touch position on the stylus tip is calibrated accurately, more accurate compensation of the pre-travel error could be applied in the inspection results. Meanwhile, time consumption on the calibration process could be reduced if the number of preset to-be-calibrated positions in the calibration is as small as possible. Thus, for precise compensation, the practical touch position on the stylus tip needs to be assigned during the inspection. In further, to reduce the calibration time, the quantity of practical touch position on the stylus tip requires to be least. A new stylus orientation planning strategy that controls the practical touch positions on the stylus tip is investigated in this paper. In terms of the strategy, a touch position graph (TPG) is proposed for the five-axis machine tool to discover the relationships between the practical touch positions, the angle combinations of rotary axis and the stylus orientations. The practical touch positions on the stylus tip and the rotation direction change of the machine tool's rotary axes can be reduced as much as possible by optimizing the stylus orientations. In further, the pre-travel error on each to-be-inspected point can be compensated by accurate calibration results and the introduction of the rotation axes error can be decreased to prove the inspection accuracy improvement. At last, an experiment is applied on the impeller to verify the proposed OMI planning strategy.